2004
DOI: 10.1063/1.1823019
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically tunable photonic crystal structure

Abstract: Articles you may be interested inTheoretical analysis for superprisming effect of photonic crystals composed of magnetic material A widely tunable refractive index in a nanolayered photonic material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
88
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(90 citation statements)
references
References 13 publications
2
88
0
Order By: Relevance
“…As a consequence, the lasing performance in such structures is expected to be greater, as conjectured by us earlier [14]. Note that the nanopillar-based structures in the wavelength range considered (1 ÷ 1.5 µm) are within the state-of-the-art fabrication possibilities, both in sandwich-like [6] and in membrane-like [18] geometry.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…As a consequence, the lasing performance in such structures is expected to be greater, as conjectured by us earlier [14]. Note that the nanopillar-based structures in the wavelength range considered (1 ÷ 1.5 µm) are within the state-of-the-art fabrication possibilities, both in sandwich-like [6] and in membrane-like [18] geometry.…”
Section: Discussionmentioning
confidence: 80%
“…This is an alternative to the known concept of tunable lasers where the resonator itself is modified, e.g. by thermal, electrooptical (using liquid crystals) or micromechanical means [16][17][18][19] to tune a given mode to have the desired frequency. One of the advantages may be that modes selected by injection seeding can be better pre-engineered to meet the desired fundamental (e.g., cavity QED) or application purposes [10].…”
Section: Introductionmentioning
confidence: 99%
“…1, 29 The largest stopband shift of 2.8 lm was exhibited by samples that were effectively strained by $40%. This stopband shift is more substantial than the 1.25 lm shift achieved by solvent swelling of lamellar photonic crystal gels outlined by Kang et al, 15 and outperforms other elastomeric 3D photonic crystals like the one reported by Fudouzi and Sawada where a 20% strain leads to a 30 nm stopband shift.…”
mentioning
confidence: 99%
“…The PC band gap is also very sensitive to mechanical deformations [12][13][14][15]. Sensitivity can be further increased by adding a micro-cavity, by deliberately introducing a local defect in the center of the PC lattice, in the form of a missing post, which creates a narrow band pass in the PC band gap.…”
Section: Introductionmentioning
confidence: 99%